The pedagogical direction as factor of determination of development of musical and figurative thinking of senior preschooler - Каряка, І.В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2012)
The article is conceded the basic aspects of influence of pedagogical directions on the forming of attitudes as factor of regulation of the process of development of musical and figurative thinking of senior preschoolers on the musical lessons.